2003
DOI: 10.1111/j.1471-0528.2003.02481.x
|View full text |Cite
|
Sign up to set email alerts
|

Levels of antibodies against cytomegalovirus and Chlamydophila pneumoniae are increased in early onset pre‐eclampsia

Abstract: The anti-CMV and anti-Chl. pneumoniae antibodies were higher in early onset pre-eclampsia than in late onset pre-eclampsia, normotensive IUGR and normal pregnancy. This may provide a pathophysiological link between pre-eclampsia and the known increased risk for subsequent atherosclerosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
76
3
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(85 citation statements)
references
References 38 publications
(68 reference statements)
4
76
3
1
Order By: Relevance
“…For example, first-trimester trophoblasts infected with CMV demonstrate reduced cell invasion, increased apoptosis (2, 79), higher expression of proinflammatory cytokines (80), and reduced HLA-G expression (81,82). CMV infection is also associated with fetal growth restriction, spontaneous pregnancy loss (82)(83)(84), and preeclampsia (85,86), all of which are outcomes that can result from insufficient placental development. HSV infection also results in loss of HLA-G (87), cell death, and reduced human chorionic gonadotropin secretion (88).…”
Section: Viral Infections and Early Placental Developmentmentioning
confidence: 99%
“…For example, first-trimester trophoblasts infected with CMV demonstrate reduced cell invasion, increased apoptosis (2, 79), higher expression of proinflammatory cytokines (80), and reduced HLA-G expression (81,82). CMV infection is also associated with fetal growth restriction, spontaneous pregnancy loss (82)(83)(84), and preeclampsia (85,86), all of which are outcomes that can result from insufficient placental development. HSV infection also results in loss of HLA-G (87), cell death, and reduced human chorionic gonadotropin secretion (88).…”
Section: Viral Infections and Early Placental Developmentmentioning
confidence: 99%
“…Association between CMV antibodies in pregnancy and development of preeclampsia is inconsistent. [34][35][36] It has been confirmed the elevated CMV antibodies level 35 and genomic DNA load in women with early onset preeclampsia was reported or confirmed. 37,38 However, Strand et al 39 reported lower anti CMV IgG seropositivity in preeclamptic women than healthy.…”
Section: Discussionmentioning
confidence: 72%
“…The risk for developing preeclampsia was confirmed by others to be associated with increased prevalence of CMV IgG together with increased CMV IgG antibodies level. 34,35 This may be explained by the fact that the increased risk for developing preeclampsia in women with specific HLA-G alleles may be combined with CMV infection. 4 It has been stated that CMV infection impairs trophoblast differentiation and invasion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[24][25][26][27][28][29][30][31][32][33][34][35] The severity of dysfunction may determine outcome and result in a spectrum of clinical presentations that share a common etiology, with severe dysfunction being associated with miscarriage and lesser dysfunction leading to preeclampsia, intrauterine growth restriction, and a predisposition to PTL. It follows that the spectrum of complications may stem from the same or related triggering factors or conditions, with the extent of complication being proportional to the variation from normal physiological levels of a biological factor (or combination of factors).…”
Section: Etiology Of Pregnancy Complicationsmentioning
confidence: 99%